Mind Mapping Technique on Junior High School Students’ Speaking Skills - Agus Setiawan; Mersi Axelina (INTERACTION: Jurnal Pendidikan Bahasa, 2022)
The objective of this research is to find out whether Mind mapping is effective or not in teaching speaking at eight-B grade of SMP N 4 Sorong Regency. Related to the objective of the research used pre-experimental quantitative research design. The design of this research was one group pre-test-post-test. The population of this research was eight grade students divide two classes that were VII A and B, the total of them were 37 students. Based on purposive sampling, the researchers chose eight B grade and which total was 10 students because the class was lack in speaking so they have low score and the students from Papua was dominant. In the collecting of data, the researchers did interview with five questions for pre-test and post-test. In analyzing the data, the researchers used SPSS 20 program to calculation the data. The result findings of the research showed that the result of N-gain was 43,77 with categorized was quite effective. In addition, the result of T-test was P-Value (0.000) < α (0.05), it means that H1 was accepted and H0 was rejected. It can be concluded that Mind Mapping Technique in Teaching Speaking was effective.